The Relationship between Emotion Comprehension and Internalizing and Externalizing Behavior in 7- to 10-Year-Old Children - Göbel, Ariane; Henning, Anne; Möller, Corina; Aschersleben, Gisa (Frontiers in Psychology, 2016)
The influence of internalizing and externalizing problems on children’s understanding of others’ emotions has mainly been investigated on basic levels of emotion comprehension. So far, studies assessing more sophisticated levels of emotion comprehension reported deficits in the ability to understand others’ emotions in children with severe internalizing or externalizing symptoms. The aim of this study was to investigate the relation between emotion comprehension and interindividual differences, with a focus on internalizing and externalizing behavior in children aged 7–10 years from the general population. A sample of 135 children was tested for emotion understanding using the Test of Emotion Comprehension. Information on internalizing and externalizing behavior was assessed with the Child Behavior Checklist 4/18. Age, bilingual upbringing, and amount of paternal working hours were significant control variables for emotion comprehension. In contrast to prior research, overall level of emotion understanding was not related to externalizing symptoms and correlated positively with elevated levels of somatic complaints and anxious/depressed symptoms. In addition, and in line with previous work, higher levels of social withdrawal were associated with worse performance in understanding emotions elicited by reminders. The present results implicate not only an altered understanding of emotions among more specific internalizing symptoms, but also that these alterations occur already on a low symptom level in a community based sample.